ANTIGENIC STRUCTURE OF THE ACTINOMYCETALES VII. : Chemical and Serological Similarities of Cell Walls From 100 Actinomycetales Strains - Kwapinski, J. B. (1964)
Kwapinski, J. B. (The University of New England, Armidale, Australia). Antigenic structure of the Actinomycetales. VII. Chemical and serological similarities of cell walls from 100 Actinomycetales strains. J. Bacteriol. 88:1211–1219. 1964.—Cell walls prepared mechanically from 100 strains of Actinomycetales were studied by chromatographic and serological methods. The cell walls of Actinomyces were found to be serologically related to those of the corynebacteria and to some strains of mycobacteria and nocardiae. The cell walls of nocardiae appeared to be more closely related to those of the mycobacteria, Streptomyces, Micromonospora, and Waksmania. The cell walls of Micromonospora and Waksmania showed certain serological similarities to those of Thermoactinomyces and nocardiae. Micropolyspora was antigenically different from other species of the Actinomycetales. Three serological groups of mycobacteria and four groups of nocardiae were distinguished.